THE ROLE OF INNOVATIVE TECHNOLOGIES IN TEACHING PHONETIC EXERCISES IN THE PRIMARY CLASS (World Bulletin of Social Sciences, 2023)
In this article, the role of using innovative technologies in the teaching of phonetic exercises is analyzed in a timely and qualitative manner. The data was collected using practical tests with students, as well as scientific articles and questionnaires.